Real options approach to multi-stage business investment decision making - Thinn Thinn Aye. (2008)
This dissertation will demonstrate how the important characteristics of investment decisions interact each other, by looking into traditional approaches (Chapter 2), applying uncertainty to traditional analysis (Chapter 3), and finally linking real options approach as a bridge between finance and strategy (Chapter 4) to make more meaningful economic decisions in the real world.